KOMPENSASI KERJA PADA KARYAWAN CV. JASA SUMBER ASAHAN MEDAN - TASIK UTAMA; RITA WIDIANI; YULIANA .; NGAJUDIN NUGROHO; DEWI ANGGRAINI (JURNAL ILMIAH SIMANTEK, 2019)
Company gives compensation in the form of salary to its employees so that their employees will feel more enthusiastic inworking. This salary will increase employee work performance in a company. The indicators for compensation are consists ofsalary, wages, bonuses, health insurance and pension funds as well as facilities to support one's career development inworking in a company. The formulation of the problem in this study is "How is the compensation given by CV. Jasa SumberAsahan Medan?" The purpose of this study is to analyze the compensation given to its employees by CV. Jasa SumberAsahan Medan. The research methodology used is a qualitative research method in which the data is obtained frominterviews with data sources used are primary data. The informants studied were employees at CV. Jasa Sumber AsahanMedan. The results showed that CV. Jasa Sumber Asahan Medan provides direct compensation in the form of salaries andbonuses. However, salaries received by employees are still below the UMP. While the indirect compensation provided by thecompany is in the form of leave taking for employees who are sick or misfortune.